Recreational use of GHB is associated with alterations of resting state functional connectivity of the central executive and default mode networks. Issue 8 (5th February 2019) - Raposo Pereira, Filipa; Zhutovsky, Paul; Mcmaster, Minni T.B.; Polderman, Nikki; de Vries, Yvon D.A.T.; van den Brink, Wim; van Wingen, Guido A.
Abstract: Gamma‐hydroxybutyrate acid (GHB) is a recreational drug with a high addictive potential. Severe side effects such as GHB‐induced coma are common and linked to increased emergency room attendances. Task‐based functional‐imaging studies have revealed an association between the regular use of GHB and multiple GHB‐induced comas, and altered neurocognitive function. However the effects of multiple GHB‐induced comas and regular GHB‐use on intrinsic brain connectivity during rest remain unknown. The study population consisted of 23 GHB‐users with ≥4 GHB‐induced comas (GHB‐Coma), 22 GHB‐users who never experienced a GHB‐induced coma (GHB‐NoComa) and 24 polydrug users who never used GHB (No‐GHB). Resting‐state scans were collected to assess resting‐state functional‐connectivity within and between the default mode network (DMN), the bilateral central executive network (CEN) and the salience network (SN). The GHB‐NoComa group showed decreased rsFC of the right CEN with a region in the anterior cingulate cortex ( p FWE = 0.048) and decreased rsFC between the right CEN and the DMN ( p FWE = 0.048) when compared with the No‐GHB group. These results suggest that regular GHB‐use is associated with decreased rsFC within the right CEN and between the right CEN and the DMN. The presence of multiple GHB‐induced comas is not associated with (additional) alterations in rsFC.